2016
DOI: 10.3390/ijerph13090845
|View full text |Cite
|
Sign up to set email alerts
|

Public’s Health Risk Awareness on Urban Air Pollution in Chinese Megacities: The Cases of Shanghai, Wuhan and Nanchang

Abstract: This study assessed the public’s health risk awareness of urban air pollution triggered by three megacities in China, and the data are the responses from a sample size of 3868 megacity inhabitants from Shanghai, Nanchang and Wuhan. Descriptive analyses were used to summarize the respondents’ demographics, perceived health risks from air pollution and sources of health-related knowledge on urban air pollution. Chi-square tests were used to examine if participants’ demographics were associated with participant’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 43 publications
12
62
1
1
Order By: Relevance
“…Therefore, they care about more and have the desire for clean air and more health living environment. However, gender was also identified to be a factor affecting people's WTP in the report [7,15], which was not confirmed in this study. A possible explanation for this discrepancy finding may be partially due to the different nature of respondent occupations.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Therefore, they care about more and have the desire for clean air and more health living environment. However, gender was also identified to be a factor affecting people's WTP in the report [7,15], which was not confirmed in this study. A possible explanation for this discrepancy finding may be partially due to the different nature of respondent occupations.…”
Section: Discussioncontrasting
confidence: 53%
“…In general, people with poor health status would have higher WTP [55] but this was not confirmed in this study. One possible explanation of this observation may be due to that health status is the feeling of a self-reported condition by participants at the survey time with no clinical testing data and reports and thus the poor health condition may be the result of many other illnesses but not necessarily due to poor air related respiratory and lung diseases [7,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of perceived health risks from air pollution in Shanghai, Wuhan, and Nanchang found that more than 57% of respondents were not satisfied with current air quality; 46% of participants expressed anxiety about exposure to polluted air. 24 Through social media, urban citizens in China are increasingly speaking out on issues that they believe are affecting their health and wellbeing. Environmental petitions and complaints have increased by more than 20% annually in recent years and mass protests for environmental issues are occurring across China.…”
Section: Executive Summarymentioning
confidence: 99%
“…Fortunately, in the 1990s, the population began to become aware of the health of the environment, which is why urban planning has taken on a new dimension. Nowadays, in addition to economic development, urban planning aims to achieve sustainable development and social equity [21][22][23], integrating environmental criteria in decision-making phases in order to address pollution and public health problems arising from the urbanization of large areas without adequate planning [24][25][26][27][28]. To achieve these objectives, urban planning has been articulated by a large amount of legislation, and a large number of tools, methodologies and techniques have been incorporated, many of which are related to geographic information systems (GISs).…”
Section: Introductionmentioning
confidence: 99%